Evaluation of improved genotypes of black bean Phaseolus vulgaris in Barinas and Monagas, Venezuela - A., Águeda Duran; Lambert G., Tania; Velázquez F., Roberto (Revista de Ciencias Agrícolas, 2014)
The research was developed at the La Alborada farm (Mamon Mamonal sector, municipality of Rojas, state of Barinas) and La Ceibafarm (Aparicio sector, municipality of Piar, state of Monagas) on Inceptisols soils and Entisols, respectively, during dry season fromNovember, 2011 to February, 2012.The aim of this investigation was to evaluate the agro-productive response of seven black bean genotypes: SA 029, line 13, Minita, Balina, Sesentera, Silvinera, and the Tacarigua commercial variety. A bifactorial randomized blocks design was used, the factors were the locality and the genotypes, with seven treatments and four replicas, distributed in 28 plots with a total experiment area of 554.8 m2. The sowing area was of 0.60 x 0.07 m for a total of 13200 plants. Plant height (cm), number of pods per plant, number of seeds per pod, weight of 100 seeds (g), and yield (t.ha-1) were evaluated. Yields in the state of Barinas were higher for the Balina and Tacarigua varieties, with 1.10 (t.ha-1) and 1.06 t.ha, respectively. In the state of Monagas, yields were higher for Line 13 variety with 1.92 t.ha-1, followed by Tacarigua with 1.68 t.ha-1, and Silvinera with 1.65 t.ha-1.The economic effect for all varieties per locality and between both localities was satisfactory.